Fundamental weight training: 102 exercises to start training - Sandler, D. (Human Kinetics, 2010)
With 102 exercises, each with photos and detailed explanations. The first few chapters introduce some of the basics of weight training, including the types of resistance training, gym protocol, language, and beginning stretches. The book then devotes a chapter to each of the general body parts, i.e., chest, back, legs, glutes, etc. etc. Finally the book offers up sample programs and routines and also encourages the student to develop their own program based on their personal fitness goals.